2013
DOI: 10.1021/bc400247w
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Dendrimer–DNA Complexation and Gene Delivery Vector Properties of Nitrogen-Core Poly(propyl ether imine) Dendrimer in Mammalian Cells

Abstract: Dendrimers as vectors for gene delivery were established, primarily by utilizing few prominent dendrimer types so far. We report herein studies of DNA complexation efficacies and gene delivery vector properties of a nitrogen-core poly(propyl ether imine) (PETIM) dendrimer, constituted with 22 tertiary amine internal branches and 24 primary amines at the periphery. The interaction of the dendrimer with pEGFPDNA was evaluated through UV-vis, circular dichroism (CD) spectral studies, ethidium bromide fluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 63 publications
(90 reference statements)
1
40
0
Order By: Relevance
“…In addition, plenty of tertiary amine groups of dendrimers can facilitate the endosomal escape of dendriplexes via a "proton-sponge" mechanism [115,119,120]. Up to now, PAMAM [15,16], PPI [17], and PLL [121,122], were among the most-researched traditional dendrimers in gene delivery [20,70,[123][124][125][126][127][128][129]. Haensler and coworkers [130] first reported that PAMAM dendrimers as non-viral gene vectors could efficiently express luciferase in cultured cell and found that Generation 6 (G6) PAMAM dendrimer had maximal gene transfection efficiency among G1 to G10 PAMAM dendrimers.…”
Section: Traditional Dendrimer/nucleic Acid Complexes In Gene Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, plenty of tertiary amine groups of dendrimers can facilitate the endosomal escape of dendriplexes via a "proton-sponge" mechanism [115,119,120]. Up to now, PAMAM [15,16], PPI [17], and PLL [121,122], were among the most-researched traditional dendrimers in gene delivery [20,70,[123][124][125][126][127][128][129]. Haensler and coworkers [130] first reported that PAMAM dendrimers as non-viral gene vectors could efficiently express luciferase in cultured cell and found that Generation 6 (G6) PAMAM dendrimer had maximal gene transfection efficiency among G1 to G10 PAMAM dendrimers.…”
Section: Traditional Dendrimer/nucleic Acid Complexes In Gene Therapymentioning
confidence: 99%
“…Dendrimers are a category of synthetic macromolecules with highly branched, monodispersed and well-defined tree-like architecture. The commonly used dendrimers include poly(amidoamine) (PAMAM) [15,16], poly(prophylenimine) (PPI), poly(L-lysine) (PLL) [17], triazine dendrimer [18,19], poly(ether imine) (PETIM) [20][21][22], carbosilane dendrimer [23], viologen dendrimer [24], and phosphorus dendrimer [25][26][27]. The functional nanoparticles (NPs) can be constructed based on the unique features of dendrimers for delivery of therapeutic agents [28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…The primary amine groups promote DNA cellular uptake because of their participation in DNA binding but the buried tertiary amino groups act as a proto-sponge in endosomes and enhance the release of DNA into the cytoplasm. The studies show that with increasing the size and diameter, dendrimers enhance transfection efficiency [39,40]. Recently, nitrogen-core poly(propyl ether imine) (PETIM) dendrimer DNA complexes have been investigated and results showed low toxicities and efficient gene delivery vector properties.…”
Section: Reviewmentioning
confidence: 99%
“…Recently, nitrogen-core poly(propyl ether imine) (PETIM) dendrimer DNA complexes have been investigated and results showed low toxicities and efficient gene delivery vector properties. Quantitative estimation, using luciferase assay, showed that the gene transfection was at least 100 times higher when compared to poly(ethyleneimine) branched polymer, having similar number of cationic sites as the dendrimer [40]. …”
Section: Reviewmentioning
confidence: 99%
“…Benzobromogalactose 25 (0.50 g, 0.76 mmol) in CH 2 Cl 2 (30 mL) was added to a solution of dendritic alcohol 21,26 (0.050 g, 9.6 μmol), Ag 2 CO 3 (0.20 g, 0.72 mmol) and AgClO 4 (0.050 g, 0.085 mmol), stirred for 30 h at room temperature, filtered, filtrate concentrated in vacuo and purified by column chromatography (Al 2 O 3 , CH 2 Cl 2 : MeOH = 95 : 5). The resulting product in tetrahydrofuran : MeOH (1 : 1) (10 mL) was added with NaOMe in MeOH (1 M) (0.02 mL), stirred at room temperature for 16 h, neutralized with an Amberlite ion-exchange (H + ) resin, filtered, concentrated in vacuo and the resulting solution subjected to dialysis (MW cut-off 3.5 kDa) to afford DG, as a foamy solid.…”
Section: Synthesis Of Galactose Functionalized Petim Dendrimermentioning
confidence: 99%